La dimensión humanística en la formación del contador público - Dextre Flores, José Carlos (2011)
The objective of this article is to show the importance of the humanistic approach of the accounting student considering the social orientation of accounting knowledge whose main objectives are the preparation, interpretation and assessing of the financial information of the different economical events. These reflections results from three years work devoted to the preparation and implementation of a new career program based on competences for the Facultad de Administración y Contabilidad of the Pontificia Universidad Católica del Perú (PUCP) and the result of a research about the needs and interests of the academic, social and business agents related to the accounting field. The career program adopted take the graduated of the career to prepare moral positive judgments and to understand that the occupation training is just a part of the human approach.